2001
DOI: 10.1023/a:1008306616994
|View full text |Cite
|
Sign up to set email alerts
|

Second-line chemotherapy for non-small-cell lung cancer with monthly docetaxel and weekly gemcitabine: A phase II trial

Abstract: Monthly docetaxel, combined with weekly gemcitabine, is an active and safe second-line therapy for NSCLC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…The DISTAL-2 trial will compare weekly docetaxel with combinations of weekly docetaxel plus capecitabine (Nadella et al, 2002), vinorelbine Leu et al, 2001) and gemcitabine (Kosmas et al, 2001;Spiridonidis et al, 2001); for this trial the DISTAL Investigators agreed to apply a slightly modified schedule of docetaxel (i.e. treatment for 3 consecutive weeks followed by 1 week of rest) that should be equivalent to the one studied in the DISTAL-1 trial, but more easy to combine with other cytotoxic agents.…”
Section: Discussionmentioning
confidence: 99%
“…The DISTAL-2 trial will compare weekly docetaxel with combinations of weekly docetaxel plus capecitabine (Nadella et al, 2002), vinorelbine Leu et al, 2001) and gemcitabine (Kosmas et al, 2001;Spiridonidis et al, 2001); for this trial the DISTAL Investigators agreed to apply a slightly modified schedule of docetaxel (i.e. treatment for 3 consecutive weeks followed by 1 week of rest) that should be equivalent to the one studied in the DISTAL-1 trial, but more easy to combine with other cytotoxic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Docetaxel has also been studied as a single agent or in combination in a variety of schedules including monthly, bi-weekly and weekly [14][15][16][17]. To improve antitumor activity and reduce toxicity, recent clinical trials using docetaxel as a single agent or in combination with others have focused on a weekly therapy with low doses, and this has led to an increased interest in measuring the drug at low concentrations [18].…”
Section: Introductionmentioning
confidence: 99%
“…28 The response rate was 10%, with a median survival of 6.0 months in patients receiving the docetaxel/gemcitabine combination, and 40% of patients receiving the docetaxel/vinorelbine therapy achieved stable disease, with a median survival of 8.0 months. Spiridonidis et al 29 conducted a phase II trial of monthly docetaxel and weekly gemcitabine, with an impressive 32.5% response rate, including one patient with a complete response and median survival of 8.1 months. Taken together, some of these phase II trials have shown superior antitumor activity of combination therapy over monotherapy in terms of response rate and survival time, encouraging us to conduct a clinical trial with combination chemotherapy in the second-line setting.…”
Section: Discussionmentioning
confidence: 99%